Impact of Body Mass Index and Comorbidities on Health-Related Quality of Life and Work Productivity in People With Overweight or Obesity: A Survey-Based Study in the United Kingdom - Andrea Leith; Lewis Harrison; João Diogo da Rocha Fernandes; Lise M. Hagelund; Christopher Lübker; Silvia Capucci (Journal of Health Economics and Outcomes Research)
# Background The prevalence and socioeconomic impact of obesity are increasing in the United Kingdom; however, the effects of body mass index (BMI) and comorbidities on health-related quality of life (HRQoL) and work productivity in people living with overweight or obesity (PLwO) have not been fully described.